Underdog - Sachs, Marilyn; Nang Chan Yeema (New York, USA Scholastic Inc., 1985)
When Izzy's father dies, Izzy is out to California to stay with an aunt and uncle she's never met. But Izzy doesn't fit into their sophisticated lives; they're just too busy for a quiet, lonely niece. Izzy feels like the biggest underdog in the whole world.
Keywords: Adult Fiction